Helicobacter fennelliae Bacteremia: Three Case Reports and Literature Review. Issue 18 (May 2016) - Saito, Sho; Tsukahara, Mika; Ohkusu, Kiyofumi; Kurai, Hanako
Abstract : Abstract: Helicobacter fennelliae is a gram-negative, spiral bacillus that appears as thin-spread colonies on sheep blood agar and is similar to Helicobacter cinaedi. H fennelliae is diagnosed by genetic testing, which is not readily available in all laboratories. Therefore, H fennelliae bacteremia has only been reported sporadically, and little is known about its clinical characteristics. We describe 3 cases of H fennelliae bacteremia with gastrointestinal symptoms, including nausea, vomiting, and diarrhea. Isolates could be differentiated from H cinaedi by biochemical reaction testing, including nitrate reduction and alkaline phosphatase hydrolysis. We retrospectively reviewed 24 cases of H fennelliae bacteremia reported in the literature. Most of the patients had immunosuppressive backgrounds, including solid tumors, hematological malignancies, and autoimmune diseases. Although gastrointestinal symptoms were common, cellulitis was not often observed in patients with H fennelliae bacteremia. Clinicians should bear in mind that H fennelliae may be a differential diagnosis in patients with gastrointestinal manifestations and gram-negative, spiral bacilli. In addition, biochemical reactions, such as nitrate reduction and alkaline phosphatase hydrolysis, are useful in differentiating H fennelliae from H cinaedi.